Zarządzanie wiekiem a polityka wspierania starszych pracowników. Doświadczenia polskie na tle innych krajów - Kołodziejczyk-Olczak, Izabela (Studia Demograficzne, 2014)
Population ageing is one of the most important demographic trends in modern societies. The process has broad implications in both macro- and micro-scale. In the article we focus on ageing-related challenges for enterprises. This area is very important for contemporary and future economies. Customers, employees and stakeholders of companies are getting older. In this changing environment new challenges appear including problems in hiring employees with relevant competencies, loosing organizational knowledge, employee succession, or mismatch between offered goods and market needs of changing costumers. Therefore, it becomes necessary to implement Age Management (AM) in organizations. The activities of employers in this area have to be supported by economic and legal instruments, and actions towards an increase of awareness and sensitivity to age-related issues.